الصورة الوالدية لدى الطفل اليتيم في مرحلة الكمون من خلال وضعية اختبار الرورشاخ - بن سالم خولة; داشر عبد القادر; عياد فتيحة (My University, 2018)
Our study aims to identify the nature of the parental image of the orphan child at the latency stage (06-11 years) in the Rorschach test mode (how to drop them and their perception of the parental image through the Rorschach test). This research is based on a clinical approach that allows us to identify the nature of the parental image of the orphan child. After determining the conditions of selecting our research group of age and duration of loss, we conducted a study in the primary Chalabi Youssef Baljelfa, and this study was based on the members of the research group consisting of three cases, all in the latency stage. To understand the study data, two methods were used, the preliminary interview and the Rorschach test Results : The results of the study showed that the parental image of the orphan child is negative and that it emerged through the following characteristics: - Lack of good parental image indicators. In general, the cases show a clear difficulty in expressing complete perceptions that reflect the parental image, which is also confirmed by the answers presented in Table IV and VII.Parental image, orphan child, latency stage, Rorschach test.